Improved voltage control of the electric vehicle operating as UPS in smart homes - Monteiro, Vítor Duarte Fernandes (2019)
As a contribution for sustainability, electric vehicles (EVs) are seen as one of the most effective influences in the transport sector. As complement to the challenges that entails the EVs integration into the grid considering the bidirectional operation (grid-to-vehicle and vehicle-to-grid), there are new concepts associated with the EV operation integrating various benefits for smart homes. In this sense, this paper proposes an improved voltage control of the EV operating as uninterruptible power supply (UPS) in smart homes. With the EV plugged-in into the smart home, it can act as an off-line UPS protecting the electrical appliances from power grid outages. Throughout the paper, the foremost advantages of the proposed voltage control strategy are comprehensively emphasized, establishing a comparison with the classical approach. Aiming to offer a sinusoidal voltage for linear and nonlinear electrical appliances, a pulse-width modulation with a multi-loop control scheme is used. A Kalman filter is used for decreasing significantly the time of detecting power outages and, consequently, the transition for the UPS mode. The experimental validation was executed with a bidirectional charger containing a double stage power conversion (an ac-dc interfacing the grid-side and a dc-dc interfacing the batteries- side) and a digital stage. The computer simulations and the acquired experimental results validate the proposed strategy in different conditions of operation.